Feasibility study into the suitability of collaborative robots for various manufacturing operations - Koh, Yu Wei Jonathan (2016)
In recent times, as technology advances and becomes increasingly sophisticated, robots are no longer constrained to simultaneous localization and mapping for control. A new alternative of programming robots was introduced when Microsoft released the Kinect which allowed the integration of an economical and compact camera that is able to capture 3-D coordinates in real time to manipulate them.